1993
DOI: 10.1111/j.1365-2869.1993.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

A neuronal group theory of sleep function

Abstract: A new theory of sleep function is presented within the context of the neuronal group selection hypothesis, which emphasizes that neuronal groups compete for neurons via use-dependent synaptic formation and atrophy. It is hypothesized that sleep serves to stabilize these competitive processes by providing a pattern of stimulation that serves to maintain a synaptic infrastructure upon which wakefulness-driven synaptic changes are superimposed. Sleep is 'quantal' in nature in that sleep is a statistical property … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
157
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(173 citation statements)
references
References 29 publications
14
157
0
2
Order By: Relevance
“…These results lend support to the notion that sleep is not only a global phenomenon, and that its intensity can be regulated at a regional level. 49 Consistent with this, previous studies in humans found that intermittent vibration of one hand produces a transient and small increase in SWA in the contralateral somatosensory cortex, 50 while whisker stimulation in rodents produces an increase in SWA in the contralateral somatosensory cortex. 51,52 Increases in SWA also occur in circumscribed cortical areas after learning a rotational adaptation task, 7 after TMS-induced stimulation of motor cortex, 9 or following paired associative stimulation within sensorimotor cortex, 11 while arm immobilization decreases SWA.…”
Section: Arc Stainingsupporting
confidence: 72%
“…These results lend support to the notion that sleep is not only a global phenomenon, and that its intensity can be regulated at a regional level. 49 Consistent with this, previous studies in humans found that intermittent vibration of one hand produces a transient and small increase in SWA in the contralateral somatosensory cortex, 50 while whisker stimulation in rodents produces an increase in SWA in the contralateral somatosensory cortex. 51,52 Increases in SWA also occur in circumscribed cortical areas after learning a rotational adaptation task, 7 after TMS-induced stimulation of motor cortex, 9 or following paired associative stimulation within sensorimotor cortex, 11 while arm immobilization decreases SWA.…”
Section: Arc Stainingsupporting
confidence: 72%
“…It may be associated with the reduction of regional cerebral blood flow which is known to occur during slow wave sleep (Finelli et al 2000b; for a review see Maquet 2000) as well as in the course of prolonged waking (Thomas et al 1998(Thomas et al , 2000. These findings support the hypothesis that sleep has a local, use-dependent, facet and that cerebral structures that had been particularly active during waking may exhibit more intensive signs of sleep (Horne 1993;Krueger and Obál 1993;Kattler et al 1994;Benington and Heller 1995;Borbély and Achermann 2000).Studies on regional differences in the sleep EEG are typically based on the statistical analysis of the records from several subjects. This approach emphasizes the changes common to all subjects, and tends to disregard individual differences.…”
mentioning
confidence: 89%
“…82,83 It was also proposed that sleep is influenced by prior synaptic use, and functions to alter synaptic connections, in part through the local production of somnogenic compounds that include cytokines. 84,85 Another conjecture is that sleep acts to downscale the strengths of synaptic connections, so that increases in synaptic strength during wakefulness stay below mechanistically infeasible limits. 8,26,[86][87][88][89] This hypothesis is related to the earlier demonstration that the firing by neurons and the strengths of their synapses are homeostatically increased or decreased to maintain firing rates within certain boundaries.…”
Section: Introductionmentioning
confidence: 99%